2016
DOI: 10.1007/s12035-015-9539-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of MMP-2 and Its Specific Inhibitor TIMP-2 Expression on the WHO Grade and Prognosis of Gliomas in Chinese Population: a Meta-Analysis

Abstract: So far, the prognostic value of matrix metalloproteinase 2 (MMP-2) and tissue inhibitor of matrix metalloproteinase 2 (TIMP-2) expressions in patients with gliomas has been widely reported, especially in China. But, the results were inconsistent. Thus, we conducted a meta-analysis to determine the correlation of MMP-2 and TIMP-2 expressions with the prognosis of patients with gliomas. Identical search strategies were used to search relevant literature in electronic databases updated to May 1, 2015, and odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…It was manifested that MMP-2 was expressed at low level in gliomas with small diameter and low malignancy, but it was highly expressed in malignant gliomas with larger diameter. These results are similar to the findings of other scholars (14). It can be seen that MMP-2 exerts its pathological effects by means of its abnormal expression in brain glioma.…”
Section: Discussionsupporting
confidence: 93%
“…It was manifested that MMP-2 was expressed at low level in gliomas with small diameter and low malignancy, but it was highly expressed in malignant gliomas with larger diameter. These results are similar to the findings of other scholars (14). It can be seen that MMP-2 exerts its pathological effects by means of its abnormal expression in brain glioma.…”
Section: Discussionsupporting
confidence: 93%
“…CA-IX inhibitors caused an evident decrease of MMP-2 activity, visualized as smaller and less intense degradation bands. These data are further confirmed by the release of TIMP-2, an endogenous inhibitor of the metalloprotease activity and tumor cell invasiveness [29,42,43]. In fact, an increase of TIMP-2 is observed under the same treatment condition that causes the decrease of MMP-2 activity, in both MDA-MB-231 and A549 cells.…”
Section: Discussionsupporting
confidence: 54%
“…It is reported that the co-culture of U87MG astrocytoma cells and human neural stem cell-derived astrocytes led to the induction of malignant-like phenotypes in astrocytes acquired from tumor cells by inducing the expression of GFAP, MMP-2, TGF-B1, SPARC, and CX43 [51]. Moreover, co-culturing of MSCs with U87MG simultaneously leads to a decrease in MMP inhibitor (TIMP-2) expression, indicating that U87MG could elevate a modification of the phenotype of neighboring astrocytes which may provide a significant change to the extracellular matrix of the tumor microenvironment and allow tumor invasion [52,53]. In addition, it was suggested that a certain miRNA was shared between normal and glioblastoma cells.…”
Section: Roles Of Mirnas In Glioblastomamentioning
confidence: 99%